DECISIONS RENDERED IN ABSENTIA AS A GROUND TO REFUSE THE EXECUTION OF A EUROPEAN ARREST WARRANT: EUROPEAN LEGAL STANDARDS AND IMPLEMENTATION IN CROATIAN LAW (EU and comparative law issues and challenges series (ECLIC), 2019)
The right of a person charged with a criminal offence to appear and take part in a hearing is enshrined in the right to a fair trial in Article 6 of the European Convention on Human Rights and Fundamental Freedoms. A trial in absentia is allowed only exceptionally, and in the member states of the European Union it is traditionally regulated under very different legal regimes. This has been an obstacle to the full implementation of the principle of mutual recognition of final judicial decisions and therefore to efficient judicial cooperation in criminal matters. In order to provide clear common grounds allowing the execution of a European arrest warrant even when the person subject to it was absent at the trial, Framework Decision 2009/299/JHA, amending Framework Decision 2002/584/JHA, defined the conditions under which a decision rendered at such a trial may be used as a ground to refuse the execution of a European arrest warrant. These conditions are the subject of this paper. Besides theoretical and normative analysis, the research includes the case law of the Court of Justice of the European Union, balancing between the efficiency of judicial cooperation and respect for fundamental human rights, as well as defining the notion of “the trial resulting in the decision” and specifying when the person was “summoned in person”, or “by other means actually received official information of the scheduled date and place of that trial”, since the right to take part in the trial may be waived. The research also includes an analysis of Croatian legislation and the jurisprudence of the Supreme Court of the Republic of Croatia in the same matter and an assessment of theimplementation of European legal standards in Croatian law.